PENGUATAN ASAS HUKUM NEGARA SEBAGAI JAMINAN MEMPERKOKOH NILAI PERSATUAN DAN KESATUAN - Nunung Nugroho (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2020)
The principle of law as a crystallization of the values that live in society, of course, must be in accordance with the conditions in which the community is located. In this case, of course, the principles of the Indonesian people must be in accordance with the values contained in the associations and the outlook of life of the nation itself; namely Pancasila as a source of legal principles for the Indonesian nation. In general, law is positioned as a tool to achieve the goals of the State, thus it is a tool or means and steps that can be used by the government to create a national legal system in order to achieve the ideals of the nation. It is the principle of unity and oneness that can achieve the goals expected by the Indonesian nation, namely a just and prosperous society or in the words of wisdom